Identification of Microbial Contamination in Street Food Around Universitas Negeri Medan - Larasati Arum Utami; Idramsa Idramsa; Artika Rindiani; Najwa Liliana; Nita Maya Sari Pane; Santaro Marito Nadeak (Journal of Innovative and Creativity, 2025)
Street food remains a popular choice for students due to its affordability and convenience. Its rapid preparation and service contribute to its ongoing popularity. The university, including Universitas Negeri Medan, is often surrounded by numerous street vendors offering a diverse range of foods, predominantly made from meat and flour. However, the open exposure of these foods and insufficient sanitation practices pose a heightened risk of contamination by harmful microorganisms. This study examines bacterial contamination in processed meat-based street foods sold near Universitas Negeri Medan, with a focus on items such as meatballs, grilled meatballs, and batagor. Microbiological examination involved isolating bacteria using selective and differential culture media, particularly Eosin Methylene Blue Agar (EMBA). Subsequent identification was carried out using Gram staining to determine cell morphology and SIM (Sulfide Indole Motility) medium for motility assessment in the microbiology lab at Universitas Negeri Medan. Findings revealed contamination predominantly in grilled meatballs, with bacteria belonging to the Enterobacteriaceae family detected. These isolates were characterized as Gram-negative, rod-shaped, and motile microorganisms. The presence of such bacteria raises serious concerns about food safety. It emphasizes the need for improved hygienic practices and rigorous food safety control measures in street food vending areas around the university. Implementing these measures is essential to safeguard student health and maintain the standard of street food quality on campus.